PENINGKATAN KAPASITAS MANAJERIAL UMKM MELALUI PELATIHAN MANAJEMEN USAHA BERBASIS PRAKTIS DI DESA MOJOSARI MANTUP LAMONGAN - Kuswanto ,; Sofia Tri Septiawati; Ratna Nurdiana; Sutarum ,; Dita Pratama (Fakultas Sosial dan Ilmu Politik Universitas Wiraraja, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the village community economy, particularly as a primary source of income and job creation. However, many MSME actors still face various challenges in business management, especially in managerial aspects such as business planning, resource organisation, financial record keeping, and effective marketing strategies. These limitations in knowledge and skills impact the productivity and competitiveness of the business. Therefore, this community service activity aims to enhance the managerial capacity of MSME actors through practical business management training in Mojosari Village, Mantup District, Lamongan Regency. The implementation method includes the stages of identifying needs, designing training materials, conducting participatory training, intensive mentoring, and evaluating the results of the activities. The results show an improvement in the understanding and skills of MSME actors in managing their businesses more systematically and structurally, particularly in preparing simple bookkeeping, managing operations, and utilising more adaptive marketing strategies. In addition, there has been a shift in the mindset of business actors towards a more professional managerial orientation. This programme is expected to promote business sustainability, enhance MSME performance, and strengthen the economic competitiveness of the community at the local level.